Latency Minimization for Secure Intelligent Reflecting Surface Enhanced Virtual Reality Delivery Systems - Zhou, Yi; Pan, Cunhua; Yeoh, Phee Lep; Wang, Kezhi; Ma, Zheng; Vucetic, Branka; Li, Yonghui (IEEE wireless communications letters, 2022)
This letter investigates a virtual reality (VR) delivery system, where the original VR contents requested by all users are stored at the macro base station (MBS). To reduce latency, MBS can either transmit the original VR data or the computed VR data to multiple users aided by an intelligent reflecting surface (IRS) to prevent attacks from an eavesdropper with imperfect channel state information (CSI). We jointly optimize the transmission policies, MBS transmit power, IRS phase shift and computing frequency to minimize the latency over all users subject to security constraint. Numerical results validate the robustness of our proposed algorithm.